Real-world efficacy of deep TMS for obsessive-compulsive disorder: Post-marketing data collected from twenty-two clinical sites. (May 2021) - Roth, Yiftach; Tendler, Aron; Arikan, Mehmet Kemal; Vidrine, Ryan; Kent, David; Muir, Owen; MacMillan, Carlene; Casuto, Leah; Grammer, Geoffrey; Sauve, William; Tolin, Kellie; Harvey, Steven; et al.
Abstract: Background: Deep transcranial magnetic stimulation (dTMS) with the H7-coil was FDA cleared for obsessive-compulsive disorder (OCD) in August 2018 based on multicenter sham-controlled studies. Here we look at the efficacy of dTMS for OCD in real world practices. Methods: All dTMS clinics were asked to supply their data on treatment details and outcome measures. The primary outcome measure was response, defined by at least a 30% reduction in the Yale Brown Obsessive Compulsive Scale (YBOCS) score from baseline to endpoint. Secondary outcome measures included first response, defined as the first time the YBOCS score has met response criteria, and at least one-month sustained response. Analyses included response rate at the endpoint (after 29 dTMS sessions), number of sessions and days required to reach first response and sustained response. Results: Twenty-two clinical sites with H7-coils provided data on details of treatment and outcome (YBOCS) measures from a total of 219 patients. One-hundred-sixty-seven patients who had at least one post-baseline YBOCS measure were included in the main analyses. Overall first and sustained response rates were 72.6% and 52.4%, respectively. The response rate was 57.9% in patients who had YBOCS scores after 29 dTMS sessions. First response was achieved in average after 18.5 sessions (SD = 9.4) or 31.6 days (SD = 25.2). Onset of sustained one-month response was achieved in average after 20 sessions (SD = 9.8) or 32.1 days (SD = 20.5). Average YBOCS scores demonstrated continuous reduction with increasing numbers of dTMS sessions. Conclusions: In real-world clinical practice, the majority of OCD patients benefitted from dTMS, and the onset of improvement usually occurs within 20 sessions. Extending the treatment course beyond 29 sessions results in continued reduction of OCD symptoms, raising the prospect of value for extended treatment protocols in non-responders.